The correlation Between Motivation and Self-Confidence on Students’ Speaking Performance at Islamic Religion Education Study Program Faculty of Tarbiyah IAIN Kendari - Zalili Sailan; Yazid A.R.G Yazid A.R.G; Normawati Normawati (ELT-Lectura, 2017)
This study aimed to find out: (1) the correlation between motivation and students’ speakingperformance; (2) the correlation between self-confidence and students’ speaking performance; (3) thesimultaneous contributed of motivation and self-confidence toward speaking performance; (4) which variableserves as the better predictor on speaking performance. Population of the study was 520 university students.Samples were determined using, firstly, a stratified random sampling; secondly simple random sampling, theresulting in 84 samples of the second, the fourth, the sixth, and eighth semester of Islamic religion educationstudy program Tarbiyah Faculty of IAIN Kendari in academic year 2015/2016. Data analyzed descriptively byconducting correlational design and multiple linear regressions using the SPSS 22. Data were collected by usingquestionnaires, speaking test and interview. The result finding showed that (1) there was a significant correlationbetween motivation and speaking performance. The contribution of motivation on speaking performance 59,1%,the correlation both of them ,769.** (2) there was significant correlation of Self-confidence on speakingperformance that’s accounts for 74,6%, and the correlation both of them ,864.** (3) motivation and selfconfidencecontributed simultaneously toward speaking performance 79, 5%, R² is 0,795. and the rest 29,1%accounted for the other variable. (4) this can be showed self-confidence is better predictor on speakingperformance than motivation.